2002
DOI: 10.1080/02652030210157709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dietary exposure of rat to di(2-ethyl hexyl) phthalate on their metabolic efficiency

Abstract: The nutritional impact of di(2-ethyl hexyl) phthalate (DEHP), specifically its energy efficiency and nitrogen utilization, was studied in the experimental rat. Groups of male Wistar rats were fed over 21 days with a standard diet alone or a standard diet supplemented with 2% (w/w) DEHP. Food intake, body weight and nitrogen compounds excretion were measured daily. The composition and energetic content of the carcass were determined in animals of both dietary groups after the feeding period, as well as in a sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…This may suggest differences in DEHP toxicokinetics by route of exposure (ingestion vs. intravenous), although evidence for this has not been shown in other studies to date. In another study in rats fed a DEHP-contaminated diet (2%) for 21 days, Bernal et al (2002) reported no difference in T 4 levels between exposed and control groups. However, serum T 4 levels were lower in exposed rats (3.44 ± 0.53 ng/mL) than in controls (4.20 ± 0.58 ng/mL); the lack of statistical significance may have been due to a small number of animals in each group ( n = 12 and 7, respectively).…”
Section: Discussionmentioning
confidence: 91%
“…This may suggest differences in DEHP toxicokinetics by route of exposure (ingestion vs. intravenous), although evidence for this has not been shown in other studies to date. In another study in rats fed a DEHP-contaminated diet (2%) for 21 days, Bernal et al (2002) reported no difference in T 4 levels between exposed and control groups. However, serum T 4 levels were lower in exposed rats (3.44 ± 0.53 ng/mL) than in controls (4.20 ± 0.58 ng/mL); the lack of statistical significance may have been due to a small number of animals in each group ( n = 12 and 7, respectively).…”
Section: Discussionmentioning
confidence: 91%
“…We have previously reported that energy efficiency and nitrogen utilization are significantly reduced in rats fed a diet supplemented with 2% DEHP, 5 suggesting that a higher state of catabolism in both fat and protein metabolism could characterize this metabolic imbalance. The mechanisms of cellular catabolism on DEHP-fed rats are unclear.…”
Section: Discussionmentioning
confidence: 98%
“…However, we could not exclude attribution of other chemicals to potential adverse effects on the female workers, because we only detected DEHP concentrations in the water and soil samples and they could coexpose to various chemicals in the occupational and living environments. Few studies reported that DEHP did not alter the thyroid hormone (thyroxin) level in rats (Bernal et al 2002). DEHP metabolites might alter plasma-free thyroxin and triiodothyronine, but did not change the serum TSH levels in men ).…”
Section: Discussionmentioning
confidence: 96%